2023
DOI: 10.3390/su15118924
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning Readiness Assessment Using Machine Learning Methods

Mohamed Zine,
Fouzi Harrou,
Mohammed Terbeche
et al.

Abstract: Assessing e-learning readiness is crucial for educational institutions to identify areas in their e-learning systems needing improvement and to develop strategies to enhance students’ readiness. This paper presents an effective approach for assessing e-learning readiness by combining the ADKAR model and machine learning-based feature importance identification methods. The motivation behind using machine learning approaches lies in their ability to capture nonlinearity in data and flexibility as data-driven mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Studies depict that e-learning gives rise to a competitive environment, enhances the creativity of both students and teachers, and leads to innovation (Gotthardt et al, 2006). Therefore, e-learning ecosystems have mushroomed over time at reputed educational institutions for their tremendous potential for improving the process of learning and teaching (Zine et al, 2023).…”
Section: E-learning-an Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies depict that e-learning gives rise to a competitive environment, enhances the creativity of both students and teachers, and leads to innovation (Gotthardt et al, 2006). Therefore, e-learning ecosystems have mushroomed over time at reputed educational institutions for their tremendous potential for improving the process of learning and teaching (Zine et al, 2023).…”
Section: E-learning-an Overviewmentioning
confidence: 99%
“…From businesses to education, from communication to governance, from manufacturing to agriculture, information technology is ubiquitous. Like all other sectors education has gone through drastic changes in the wake of technological advancement (Zine et al, 2023). E-learning has become the norm today.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was also revealed that various studies differ from our study in terms of gender (Adams et al, 2022;Mirabolghasemi et al, 2019;Rafique et al, 2021;Reyes et al, 2021;Scherer et al, 2021;Turgut & Balbağ, 2017). This difference in students' readiness for ERT based on gender can be explained by the fact that women and men have different learning styles and preferences (Zine et al, 2023).…”
Section: Ert Readiness Of Higher Education Studentsmentioning
confidence: 99%
“…Learning in the new normal era requires quick adapting such as setting the learning hours and implementing health protocols. The new normal era requires several new learning systems as it combines face-to-face and virtual learning (Liesveld, Petrovic, & Grohman, 2023;Zine et al, 2023). Several factors that teachers needed to consider included problems faced by teachers (40 respondents), students' enthusiasm for welcoming the new normal of learning (7 respondents), learning strategies prepared by teachers in the new normal of learning (62 respondents) and students' learning habits (37 respondents) (see Figure 3).…”
Section: Changes In Distance Learning Towards the New Normal Of Learningmentioning
confidence: 99%